Nickel-molybdenum modified cobalt molybdate composite material, preparation method thereof and neutral electrolyzed water hydrogen evolution application of nickel-molybdenum modified cobalt molybdate composite material
By modifying the cobalt molybdate composite material with nickel-molybdenum to improve the conductivity and water adsorption capacity of the catalyst in a neutral environment, the problem of insufficient catalyst activity and stability in the field of neutral electrolytic water is solved, and efficient electrolytic hydrogen analysis reaction is achieved.
Patent Information
- Application Number
- CN202410975845.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2025-04-11
AI Technical Summary
In a neutral environment, the concentration of water decomposition intermediate reactants is low, which is not conducive to the adsorption/activation of reactants by the catalyst, resulting in slow progress in the field of neutral electrolysis.
Nickel-molybdenum-molybdenum-molybdenum-molybdenum composite material is used to modify the cobalt molybdenum-molybdenum nanorod arrays modified by nanosheets on conductive substrates to enhance the conductivity and water adsorption capacity of the catalyst and improve electron transfer capacity.
High-efficiency electrolytic hydrogen analysis under neutral conditions is achieved, which reduces the overpotential, improves stability and catalytic activity, and maintains strong stability under large current conditions.
Smart Images

Figure BDA0004954486720000091 
Figure HDA0004954486730000011 
Figure HDA0004954486730000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of neutral water electrolysis hydrogen production catalysts, and in particular relates to a nickel-molybdenum modified cobalt molybdate composite material, a preparation method thereof, and an application of neutral water electrolysis hydrogen evolution. Background Art
[0002] Hydrogen has high energy density and its combustion products are zero carbon and pollution-free. Therefore, it is considered to be a new energy carrier that can be used to solve the energy crisis and reduce dependence on fossil energy. At present, most industries use natural gas steam reforming and carbon gasification reactions to produce hydrogen. In the process, a large amount of greenhouse gases such as CO2 will be released, thereby exacerbating the greenhouse effect. The electrolysis of water to produce hydrogen can not only produce high-purity hydrogen, but also directly use electricity generated by renewable energy. It is a promising and sustainable high-purity distributed hydrogen production technology. In recent years, people have been committed to developing high-performance non-precious metal catalysts to improve the efficiency of electrolyzers while controlling production costs, and have made good progress. However, both acidic electrolyzers based on proton exchange membranes and alkaline electrolyzers based on anion exchange membranes require the use of highly corrosive electrolytes, which not only cause great pollution to the environment, but also cause serious damage to the electrolyzer. Therefore, the development of water splitting catalysts that can work efficiently under mild conditions is of great significance to the field of electrolysis of water to produce hydrogen. However, the current progress in the field of neutral water electrolysis is slow, mainly because in a neutral environment, the concentration of intermediate reactants in water decomposition is low, which is not conducive to the adsorption / activation of the reactants by the catalyst. Therefore, the rational design of catalyst components and the regulation of the electronic structure of the catalyst so that it can be efficiently used in neutral water decomposition technology will provide support for the large-scale application of water electrolysis.
[0003] The water splitting process consists of two half reactions: the hydrogen evolution reaction (HER) involving two electron transfer and the oxygen evolution reaction (OER) involving four electron transfer. The development of efficient catalysts for HER will greatly promote the development of the water splitting field. Although some precious metal catalysts such as (IrO2) and platinum (Pt) have been designed for neutral HER research and have achieved good results, the low earth reserves and high cost of precious metal elements are undoubtedly not conducive to the large-scale application of water electrolysis technology. Therefore, some non-precious metal catalysts including cobalt-based, nickel-based and iron-based catalysts have also been proposed and used in pH-neutral HER, but these catalysts have high overpotentials (10mA / cm 2 The overpotential is higher than 100mV at a current density of 100mV and the stability is poor (less than 50 hours), which means it is still far from practical application. Among non-precious metal catalysts, cobalt-molybdenum-based catalysts are considered to be a material with HER activity comparable to precious metals. However, the cobalt element in cobalt-molybdenum-based catalysts is easily precipitated during the neutral water decomposition reaction, resulting in extremely poor stability and cannot be used in practice. Summary of the invention
[0004] The purpose of the present invention is to provide a nickel-molybdenum-modified cobalt molybdate composite material, a preparation method thereof, and neutral water electrolysis hydrogen evolution application. The composite material has a stable structure, abundant active sites, good conductivity, and strong water adsorption capacity. When used in the electrolysis of water for hydrogen evolution reaction under neutral conditions, the overpotential is low, and it still has strong stability under high current conditions, showing excellent catalytic activity and stability, simple and efficient preparation, and has important application prospects.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] Provided is a nickel-molybdenum-modified cobalt molybdate composite material, comprising a conductive substrate and nickel-molybdenum-modified cobalt molybdate grown on the conductive substrate, wherein the nickel-molybdenum-modified cobalt molybdate is in the form of a nanosheet-modified cobalt molybdate nanorod array, wherein the nanosheet has a thickness of 5-80 nm and the nanorod has a diameter of 0.1-1 μm.
[0007] According to the above scheme, the conductive substrate is any one of metal nickel foam, metal nickel mesh, metal nickel felt, stainless steel felt, metal nickel-iron foam, metal copper foil, metal copper foam, metal iron foam, metal titanium mesh, carbon cloth, carbon paper, graphite felt, carbon fiber and various carbon materials obtained by calcining fruit shells and mollusk shells.
[0008] According to the above scheme, the nickel-molybdenum modified cobalt molybdate composite material is prepared by mixing a conductive substrate with urea, ammonium fluoride, cobalt salt, molybdenum salt, nickel salt and water and then conducting a hydrothermal reaction.
[0009] A method for preparing the nickel-molybdenum-modified cobalt molybdate composite material is provided, comprising the following steps:
[0010] The conductive substrate is placed in a mixed solution of urea, ammonium fluoride, cobalt salt, molybdenum salt, nickel salt and water, and a hydrothermal method is used to react to grow a nanosheet-modified CoMoO4 nanorod array on the conductive substrate to obtain a nickel-molybdenum-modified cobalt molybdate composite material.
[0011] According to the above scheme, after the reaction is completed, cool to room temperature, take out, wash and dry.
[0012] According to the above scheme, the cobalt salt is any one of Co(NO3)2, CoSO4, CoCO3, Co3(PO4)2 and CoCl2.
[0013] According to the above scheme, the molybdenum salt is any one of Na2MoO4, K2MoO4 and (NH4)2MoO4.
[0014] According to the above scheme, the nickel salt is any one of Ni(NO3)2, NiSO4 and NiCl2.
[0015] According to the above scheme, the molar ratio of the cobalt element in the cobalt salt to the molybdenum element in the molybdenum salt is 1:0.3-1.2, preferably 1:0.4-0.7.
[0016] According to the above scheme, the molar ratio of the cobalt element in the cobalt salt to the nickel element in the nickel salt is 1:0.25-1, preferably 1:0.3-0.6.
[0017] According to the above scheme, in the mixed solution, the concentration of cobalt in the cobalt salt is 0.005-0.200 mol / L, preferably 0.09-0.16 mol / L. The appropriate concentration of Co and the ratio between metal elements are beneficial to the performance of neutral water electrolysis hydrogen evolution reaction.
[0018] According to the above scheme, the molar ratio of urea, ammonium fluoride and cobalt element in cobalt salt is 1:0.4-0.8:0.6-1.5.
[0019] According to the above scheme, in the mixed solution, the concentration of molybdenum element in the molybdenum salt is 0.005-0.200 mol / L; the concentration of nickel element in the nickel salt is 0.001-0.050 mol / L; the concentration of urea is 0.01-0.20 mol / L, and the concentration of ammonium fluoride is 0.01-0.20 mol / L.
[0020] According to the above scheme, the temperature of the hydrothermal reaction is 100-200°C.
[0021] According to the above scheme, the hydrothermal reaction time is 2-20h.
[0022] Provided is an application of the nickel-molybdenum modified cobalt molybdate composite material in a hydrogen evolution reaction by electrolysis of water under neutral conditions.
[0023] According to the above scheme, the nickel-molybdenum-modified cobalt molybdate composite material is used as a hydrogen evolution electrode to carry out a water hydrogen evolution reduction reaction in a neutral three-electrode system.
[0024] Preferably, in the neutral three-electrode system, the carbon rod serves as the counter electrode and the calomel electrode serves as the reference electrode.
[0025] Preferably, in the neutral three-electrode system, the neutral electrolyte is phosphate, sulfate or chloride, and the concentration of the neutral electrolyte is 1-6 mol / L;
[0026] Compared with the prior art, the present invention is beneficial in that:
[0027] 1. The present invention provides a nickel-molybdenum-modified cobalt molybdate composite material, comprising a conductive substrate and nickel-molybdenum-modified cobalt molybdate grown on the conductive substrate, wherein the nickel-molybdenum-modified cobalt molybdate is in the form of a cobalt molybdate nanorod array modified with nanosheets; on the one hand, the conductivity and water adsorption capacity of CoMoO4 are enhanced, and the electron transfer capacity is improved, thereby promoting the reaction kinetics of the hydrogen evolution reaction, enhancing the efficiency of the electrocatalytic water reduction reaction, and realizing efficient electrolysis of water for hydrogen evolution under neutral conditions; on the other hand, the stability of the composite material itself is improved, the precipitation of metal elements during the reaction process is reduced, and the composite material still has strong stability under the condition of a large current in a neutral reaction system; wherein when applied to the electrolysis of water for hydrogen evolution reaction under neutral conditions, the composite material has a high conductivity at 10 and 500 mA cm -2 At a current density of 2.5 MHz and 4.5 MHz, the required HER overpotential in neutral aqueous solution is as low as 46 and 454 mV, and it can operate for 1000 and 300 hours, respectively. There is no obvious attenuation in the neutral water reduction performance, which has important application prospects.
[0028] 2. The present invention provides a method for preparing a nickel-molybdenum modified cobalt molybdate composite material. By a one-step hydrothermal method, nickel element is introduced during the growth process of CoMoO4 nanorod array, and finally a CoMoO4 nanorod array modified with nanosheets is obtained. The preparation method is simple and efficient, the conditions are mild, and no calcination is required. The obtained composite material has a stable structure and exhibits excellent catalytic activity and stability as a neutral water reduction electrode, which is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Scanning electron microscope (SEM) images of the nanosheet / CoMoO4 nanorod structure (denoted as NiMo / CoMoO4) array grown on the nickel foam substrate after the hydrothermal reaction in Example 1 at different magnifications.
[0030] Figure 2 Scanning electron microscope (SEM) images of cobalt molybdate (denoted as CoMoO4) nanorod arrays grown on a nickel foam substrate after a hydrothermal reaction in Comparative Example 1 at different magnifications.
[0031] Figure 3 This is the scanning electron microscope (SEM) image and energy dispersive spectrum (EDS) element distribution diagram of Ni, Co, Mo and O elements of NiMo / CoMoO4 obtained in Example 1.
[0032] Figure 4(a) is the X-ray diffraction (XRD) pattern of CoMoO4 and NiMo / CoMoO4; (b) is the Raman spectrum (Raman) comparison diagram of CoMoO4 and NiMo / CoMoO4; (c) is the Fe 2p energy level diagram of the X-ray photoelectron spectroscopy (XPS) of CoMoO4 and NiMo / CoMoO4; (d) is the Ni 3d energy level diagram of the XPS of NiMo / CoMoO4.
[0033] Figure 5 Comparison of the HER performance of NiMo / CoMoO4 in neutral electrolyte (1 mol / L phosphate buffer (PBS)) and other samples: (a) is the linear sweep voltammetry (LSV) curve; (b) is the overpotential comparison at different current densities; (c) is the Tafel slope diagram; (d) is the electrochemical impedance spectroscopy (EIS).
[0034] Figure 6 (a) is the voltage stability curve of NiMo / CoMoO4 at low current density in neutral electrolyte (1 mol / L PBS); (b) is the voltage stability curve of NiMo / CoMoO4 at high current density in neutral electrolyte (1 mol / L PBS). DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0036] The embodiment of the present invention provides a nickel-molybdenum-modified cobalt molybdate composite material, comprising a conductive substrate and a nickel-molybdenum-modified cobalt molybdate grown on the conductive substrate, wherein the nickel-molybdenum-modified cobalt molybdate is in the form of a cobalt molybdate nanorod array modified with nanosheets, wherein the thickness of the nanosheets is 5-80 nm, and the diameter of the nanorods is 0.1-1 μm.
[0037] In some specific embodiments, the conductive substrate is any one of metal nickel foam, metal nickel mesh, metal nickel felt, stainless steel felt, metal nickel-iron foam, metal copper foil, metal copper foam, metal iron foam, metal titanium mesh, carbon cloth, carbon paper, graphite felt, carbon fiber, and various carbon materials obtained by calcining fruit shells and mollusk shells.
[0038] The embodiment of the present invention also provides a method for preparing the nickel-molybdenum-modified cobalt molybdate composite material, comprising the following steps:
[0039] The conductive substrate is placed in a mixed solution of urea, ammonium fluoride, cobalt salt, molybdenum salt, nickel salt and water, and a hydrothermal method is used to react to grow a nanosheet-modified CoMoO4 nanorod array on the conductive substrate to obtain a nickel-molybdenum-modified cobalt molybdate composite material.
[0040] In some specific embodiments, the cobalt salt is any one of Co(NO3)2, CoSO4, CoCO3, Co3(PO4)2 and CoCl2; the molybdenum salt is any one of Na2MoO4, K2MoO4 and (NH4)2MoO4; the nickel salt is any one of Ni(NO3)2, NiSO4 and NiCl2.
[0041] In some specific embodiments, the molar ratio of the cobalt element in the cobalt salt to the molybdenum element in the molybdenum salt is 1:0.3-1.2, preferably 1:0.4-0.7.
[0042] In some specific embodiments, the molar ratio of the cobalt element in the cobalt salt to the nickel element in the nickel salt is 1:0.25-1, preferably 1:0.3-0.6.
[0043] In some specific embodiments, the molar ratio of cobalt element in urea, ammonium fluoride and cobalt salt is 1:0.4-0.8:0.6-1.5.
[0044] In some specific embodiments, in the mixed solution, the concentration of the cobalt element in the cobalt salt is 0.005 to 0.200 mol / L, preferably 0.09 to 0.16 mol / L.
[0045] In some specific embodiments, in the mixed solution, the concentration of molybdenum element in the molybdenum salt is 0.005-0.200 mol / L; the concentration of nickel element in the nickel salt is 0.001-0.050 mol / L; the concentration of urea is 0.01-0.20 mol / L, and the concentration of ammonium fluoride is 0.01-0.20 mol / L.
[0046] In some specific embodiments, the hydrothermal reaction is carried out at a temperature of 100-200° C. and for a time of 2-20 h.
[0047] The embodiment of the present invention also provides an application of the nickel-molybdenum-modified cobalt molybdate composite material in a hydrogen evolution reaction in water electrolysis under neutral conditions.
[0048] In some specific embodiments, the nickel-molybdenum-modified cobalt molybdate composite material is used as a hydrogen evolution electrode to carry out a water hydrogen evolution reduction reaction in a neutral three-electrode system.
[0049] Preferably, in the neutral three-electrode system, the carbon rod serves as the counter electrode and the calomel electrode serves as the reference electrode.
[0050] Preferably, in the neutral three-electrode system, the neutral electrolyte is phosphate, sulfate or chloride, and the concentration of the neutral electrolyte is 1-6 mol / L; more preferably, the pH of the solution is 7.
[0051] The following are specific embodiments.
[0052] Example 1
[0053] Provided is a method for preparing a nickel-molybdenum-modified cobalt molybdate composite material, comprising the following steps:
[0054] A 1cm*2cm nickel foam was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for 15mins, and then the cleaned nickel foam was placed in 60mL of a mixed solution containing 0.15mol / LCoCl2, 0.05mol / L Ni(NO3)2, 0.06mol / L(NH4)2MoO4, 0.13mol / L urea and 0.08mol / L ammonium fluoride, and reacted at 120°C for 4 hours using a hydrothermal method. After the reaction was completed and cooled to room temperature, the catalyst was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60°C for 4 hours to obtain a nanosheet-modified CoMoO4 nanorod array catalyst grown on nickel foam (referred to as "NiMo / CoMoO4").
[0055] Comparative Example 1
[0056] Provided is a method for preparing a CoMoO4 nanorod array, comprising the following steps:
[0057] A 1cm*2cm nickel foam was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for 15mins, and then the cleaned nickel foam was placed in 10mL of a mixed solution containing 0.05mol / L CoCl2 and 0.05mol / L (NH4)2MoO4, and reacted at 160°C for 6 hours using a hydrothermal method. After the reaction was completed and cooled to room temperature, the catalyst was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60°C for 4 hours to obtain a CoMoO4 nanorod array catalyst grown on nickel foam (referred to as "CoMoO4").
[0058] Comparative Example 2
[0059] A method for preparing a NiMoO4 nanorod array is provided, comprising the following steps:
[0060] A 2cm*4cm nickel foam was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water in turn and ultrasonicated for 15mins. The cleaned nickel foam was then placed in 75mL of a mixed solution containing 0.1mol / L Ni(NO3)2 and 0.04mol / L(NH4)2MoO4 and reacted at 180°C for 6 hours using a hydrothermal method. After the reaction was completed and cooled to room temperature, the catalyst was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60°C for 4 hours to obtain a NiMoO4 nanosheet array catalyst grown on nickel foam (referred to as "NiMoO4").
[0061] Figure 1 and Figure 2 The SEM images of NiMo / CoMoO4 obtained in Example 1 and CoMoO4 obtained in Comparative Example 1 are respectively, and the specific steps are to observe the sample morphology of the prepared catalyst on JEOL JSM-7900, and the electron beam intensity is 12.6keV. It can be seen that NiMo / CoMoO4 is a morphology of nanosheets modified nanorod arrays, wherein the thickness of the nanosheets is 5-80nm, and the size of the nanorods is 0.1-1μm. And CoMoO4 is a morphology of nanorod arrays.
[0062] Figure 3 This is the EDS element distribution diagram of the NiMo / CoMoO4 catalyst prepared in Example 1. The specific steps are to observe the morphology of the prepared catalyst on JEOL 2100F, and use energy dispersive spectroscopy equipped with QUANTAX 200-TEM model to study the distribution of each element in the catalyst. It can be seen that Ni, Co, Mo and O elements are uniformly distributed on the catalyst, successfully proving the formation of CoMoO4 and the incorporation of Ni into the catalyst.
[0063] Figure 4 (a) is the XRD spectrum of the prepared NiMo / CoMoO4 catalyst, specifically, the prepared catalyst was collected on X'PertPRO. It can be seen that NiNi (PDF#1-1266) and cobalt molybdate (PDF#21-0868) characteristic peaks; the prepared catalyst sample and the 2 Raman characterization of the sample after continuous hydrogen evolution reaction for 300 hours at a current density of Figure 4 (b) shows the comparison of Raman spectra of the sample before and after hydrogen evolution reaction. The specific steps are to collect Raman spectrum signals on HORIBA LabRAM with a laser wavelength of 832nm. It can be found that the sample has Co-O, Ni-O, MO-O and Mo-O-Co Raman signals, indicating the successful synthesis of nickel-molybdenum modified cobalt molybdate NiMo / CoMoO4. Figure 4(c) shows the XPS Ni 2p level spectrum comparison of the sample before and after the hydrogen evolution reaction. It can be found that after the reaction, the Ni 2+ The peak moves to lower energy. Figure 4 (d) shows the comparison of Mo 3d energy level spectra of XPS of NiMo / CoMoO4. The 3d split peak spacing of Mo before the reaction is 3.52eV, indicating that the oxidation state of Mo element is +6. In the sample after continuous hydrogen evolution reaction, Mo element has two valence states of +4 and +6. This is because the hydrogen evolution electrode will continuously gain electrons in the electrolysis of water, thereby reducing the valence state of the catalyst. The reduction of Mo valence state is beneficial to protecting the stability of the valence state of metal Ni and Co, ensuring the catalytic activity of the catalyst. The specific steps of XPS spectrum acquisition are to collect XPS signals on the ESCALAB250XI (Thermo) system.
[0064] The NiMo / CoMoO4 and CoMoO4 catalysts prepared in Example 1 and Comparative Example 1 were respectively tested for their neutral water H reduction reaction performance. The steps are as follows: a three-electrode system consisting of a NiMo / CoMoO4 or CoMoO4 catalyst as a working electrode, a silver chloride electrode as a reference electrode, and a graphite rod electrode as a counter electrode was placed in a neutral electrolyte to test its water reduction performance, wherein the electrolyte was a 1 mol / L phosphate buffer solution with a solution pH of 7.
[0065] Figure 5 (a) and (b) show the linear sweep voltammetry (LSV) curves of CoMoO4, NiMo / CoMoO4 and NiMoO4 samples in 1 mol / L phosphate buffer solution and detailed HER overpotential comparison diagrams. It can be found that the HER performance of NiMo / CoMoO4 is significantly improved at 10 and 500 mA / cm 2 At current densities of 1.3 and 1.6, the required HER overpotential is only as low as 46 and 454 mV, which is much better than commercial Pt / C samples. The Tafel slopes of these samples are further calculated as follows: Figure 5 As shown in (c), the NiMo / CoMoO4 sample has a low Tafel slope of 48.88 mV / dec, indicating that NiMo / CoMoO4 is conducive to promoting faster OER reaction kinetics. At the same time, NiMo / CoMoO4 has better conductivity, thereby promoting rapid electron transfer on the catalyst, as shown in Figure 5 (d) The electrochemical impedance spectroscopy diagram shows that NiMo / CoMoO4 has a smaller charge transfer resistance.
[0066] Figure 6 (a) shows the CoMoO4 and NiMo / CoMoO4 samples in 1 mol / L PBS solution at 10 A / cm 2Comparison of stability under current density. It can be found that the stability of NiMo / CoMoO4 is greatly improved at 10mA / cm 2 At a current density of , the NiMo / CoMoO4 sample can operate stably for 1000 hours, while the performance of the CoMoO4 sample gradually decays within 20 hours of operation. Figure 6 (b) shows the CoMoO4 and NiMo / CoMoO4 samples in 1 mol / L PBS solution at 500 mA / cm 2 Stability under current density. At 500mA / cm 2 At a high current density, the NiMo / CoMoO4 sample can operate stably for more than 300 hours, demonstrating its excellent stability.
[0067] Comparative Example 3
[0068] A calcined CoMoO4-based composite material is provided, comprising the following steps:
[0069] A 1cm*2cm nickel foam was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for 15mins, and then the cleaned nickel foam was placed in 60mL of a mixed solution containing 0.15mol / L CoCl2, 0.05mol / L Ni(NO3)2, 0.06mol / L(NH4)2MoO4, 0.13mol / L urea and 0.08mol / L ammonium fluoride, and reacted at 120°C for 4 hours using a hydrothermal method. After the reaction was completed and cooled to room temperature, the catalyst was repeatedly rinsed with anhydrous ethanol and deionized water, then dried in an oven set at 60°C for 4 hours, and then calcined at 300°C in a muffle furnace for 3 hours. The resulting product was recorded as NiMo / CoMoO4-1.
[0070] The HER overpotential performance of NiMo / CoMoO4-1 obtained in this comparative example was tested. The results showed that at 10 mA / cm 2 Overpotential 93mV, 500mA / cm 2 The overpotential is 612mV.
[0071] Example 2
[0072] Provided is a method for preparing a nickel-molybdenum-modified cobalt molybdate composite material, comprising the following steps:
[0073] A 1cm*2cm nickel copper foam was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for 15mins, and then the cleaned nickel foam was placed in 60mL solution containing 0.2mol / L Co(NO3)2, 0.05mol / L NiCl2, 0.06mol / L K2MoO4, 0.13mol / L urea and 0.08mol / L ammonium fluoride, and reacted at 200℃ for 2 hours by hydrothermal method. After the reaction was completed and cooled to room temperature, the catalyst was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60℃ for 4 hours to obtain a nanosheet-modified CoMoO4 nanorod array catalyst grown on nickel foam (referred to as "NiMo / CoMoO4").
[0074] The prepared nanosheet-modified CoMoO4 nanorod array was used as a working electrode, a silver chloride electrode as a reference electrode, and a graphite rod electrode as a counter electrode to form a three-electrode system and placed in a neutral electrolyte to test its water reduction performance. The electrolyte was 6 mol / L sodium chloride. The sample was tested at 10 and 500 mA / cm 2 The overpotential of neutral water reduction at current density is shown in Table 1.
[0075] Example 3
[0076] Provided is a method for preparing a nickel-molybdenum-modified cobalt molybdate composite material, comprising the following steps:
[0077] The CoMoO4 nanorod array modified by nanosheets was synthesized by hydrothermal method. A 1cm*2cm nickel mesh was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water in turn and ultrasonicated for 15mins. Then the cleaned nickel foam was placed in 60mL solution containing 0.09mol / L CoCO3, 0.05mol / L Ni(NO3)2, 0.06mol / L(NH4)2MoO4, 0.13mol / L urea and 0.08mol / L ammonium fluoride, and reacted by hydrothermal method at 140℃ for 16 hours. After the reaction was completed and cooled to room temperature, the catalyst was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60℃ for 4 hours to obtain a nanosheet-modified CoMoO4 nanorod array catalyst grown on nickel foam (referred to as "NiMo / CoMoO4").
[0078] The prepared nanosheet-modified CoMoO4 nanorod array was used as the working electrode, the silver chloride electrode as the reference electrode, and the graphite rod electrode as the counter electrode to form a three-electrode system and placed in a neutral electrolyte to test its water reduction performance. The electrolyte was 5 mol / L phosphate buffer. The sample was tested at 10 and 500 mA / cm 2The overpotential of neutral water reduction at current density is shown in Table 1.
[0079] Example 4
[0080] Provided is a method for preparing a nickel-molybdenum-modified cobalt molybdate composite material, comprising the following steps:
[0081] A 1cm*2cm nickel-iron foam was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for 15mins, and then the cleaned nickel foam was placed in 60mL solution containing 0.07mol / L CoCl2, 0.05mol / L NiCl2, 0.06mol / L Na2MoO4, 0.13mol / L urea and 0.08mol / L ammonium fluoride, and reacted at 180°C for 12 hours using a hydrothermal method. After the reaction was completed and cooled to room temperature, the catalyst was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60°C for 4 hours to obtain a nanosheet-modified CoMoO4 nanorod array catalyst grown on nickel foam (referred to as "NiMo / CoMoO4").
[0082] The prepared nanosheet-modified CoMoO4 nanorod array was used as the working electrode, the silver chloride electrode as the reference electrode, and the graphite rod electrode as the counter electrode to form a three-electrode system and placed in a neutral electrolyte to test its water reduction performance. The electrolyte was 1 mol / L phosphate buffer. The sample was tested at 10 and 500 mA / cm 2 The overpotential of neutral water reduction at current density is shown in Table 1.
[0083] Example 5
[0084] Provided is a method for preparing a nickel-molybdenum-modified cobalt molybdate composite material, comprising the following steps:
[0085] A 1cm*2cm stainless steel felt was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for 15mins, and then the cleaned nickel foam was placed in 60mL solution containing 0.12mol / L CoCl2, 0.05mol / L NiSO4, 0.06mol / L K2MoO4, 0.13mol / L urea and 0.08mol / L ammonium fluoride, and reacted at 150°C for 8 hours using a hydrothermal method. After the reaction was completed and cooled to room temperature, the catalyst was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60°C for 4 hours to obtain a nanosheet-modified CoMoO4 nanorod array catalyst grown on nickel foam (referred to as "NiMo / CoMoO4").
[0086] The prepared nanosheet-modified CoMoO4 nanorod array was used as the working electrode, the silver chloride electrode as the reference electrode, and the graphite rod electrode as the counter electrode to form a three-electrode system and placed in a neutral electrolyte to test its water reduction performance. The electrolyte was 2 mol / L potassium sulfate. The sample was tested at 10 and 500 mA / cm 2 The overpotential of neutral water reduction at current density is shown in Table 1.
[0087] Table 1. Summary of neutral water reduction performance of NiMo / CoMoO4 samples prepared in Examples 1-6
[0088]
[0089] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.
Claims
1. A nickel-molybdenum-modified cobalt molybdate composite material, characterized in that: The invention comprises a conductive substrate and nickel-molybdenum-modified cobalt molybdate grown on the conductive substrate. The nickel-molybdenum-modified cobalt molybdate is in the shape of a nano-sheet-modified cobalt molybdate nano-rod array, wherein the thickness of the nano-sheet is 5-80nm and the diameter of the nano-rod is 0.1-1μm.
2. The composite material according to claim 1, characterized in that The conductive substrate is any one of metal nickel foam, metal nickel mesh, metal nickel felt, stainless steel felt, metal nickel-iron foam, metal copper foil, metal copper foam, metal iron foam, metal titanium mesh, carbon cloth, carbon paper, graphite felt, carbon fiber, and various carbon materials obtained by calcining fruit shells and mollusk shells.
3. The composite material according to claim 1, characterized in that The nickel-molybdenum-modified cobalt molybdate composite material is prepared by mixing a conductive substrate with urea, ammonium fluoride, cobalt salt, molybdenum salt, nickel salt and water and then carrying out a hydrothermal reaction.
4. A method for preparing the nickel-molybdenum-modified cobalt molybdate composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The conductive substrate is placed in a mixed solution of urea, ammonium fluoride, cobalt salt, molybdenum salt, nickel salt and water, and a hydrothermal method is used to react to grow a nanosheet-modified CoMoO4 nanorod array on the conductive substrate to obtain a nickel-molybdenum-modified cobalt molybdate composite material.
5. The preparation method according to claim 4, characterized in that: The cobalt salt is any one of Co(NO3)2, CoSO4, CoCO3, Co3(PO4)2 and CoCl2; the molybdenum salt is any one of Na2MoO4, K2MoO4 and (NH4)2MoO4; the nickel salt is any one of Ni(NO3)2, NiSO4 and NiCl2.
6. The preparation method according to claim 4, characterized in that: The molar ratio of the cobalt element in the cobalt salt to the molybdenum element in the molybdenum salt is 1:0.3-1.2; the molar ratio of the cobalt element in the cobalt salt to the nickel element in the nickel salt is 1:0.25-1; and the concentration of the cobalt element in the cobalt salt is 0.005-0.200 mol / L.
7. The preparation method according to claim 4, characterized in that: The molar ratio of cobalt element in urea, ammonium fluoride and cobalt salt is 1:0.4-0.8:0.6-1.
5.
8. The preparation method according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 100-200° C. and the time is 2-20 hours.
9. Use of the nickel-molybdenum-modified cobalt molybdate composite material according to any one of claims 1 to 3 in hydrogen evolution reaction under neutral conditions of water electrolysis.
10. The use according to claim 9, characterized in that: The nickel-molybdenum modified cobalt molybdate composite material is used as a hydrogen evolution electrode to carry out a water hydrogen evolution reduction reaction in a neutral three-electrode system.
Citation Information
Patent Citations
Preparation method and application of core-shell structured cobalt molybdate@ nickel cobaltate material
CN107068420A
Cobalt phosphate and molybdenum trioxide composite nanorod array three-dimensional electrode material and preparation method and application thereof
CN113699552A
Ultrathin bimetallic molybdate nanosheet coated nanotube heterostructure material and preparation method and application thereof
CN113818041A
Urine containers for male drivers
KR1020210014879A
Method and apparatus for object proximity analysis on the mixed reality network
KR102620856B1